Expanding the welfare system: a proposal for reform - Jonathan Michael Orszag; Dennis J. Snower (The welfare state in Europe: Challenges and reforms, 1998)
The proposal involves the establishment of 'welfare accounts' for every person in a country. There are to be four accounts: a retirement account (covering pensions), an unemployment account (covering unemployment support), a human capital account (covering education and training), and a health account (covering insurance against sickness and disability). Instead of the current welfare state systems - where welfare services are financed predominantly out of general taxes - people would make ongoing, mandatory contributions to each of these welfare accounts. The balances in these accounts would cover people's major welfare needs. The government is to set mandatory minimum contribution rates and maximum withdrawal rates from the accounts. The government is to have two budgetary systems: one in which non-welfare expenditures are financed through the existing array of taxes, and another system in which the public-sector expenditures on welfare services are financed through payments from people's welfare accounts. The government would be able to redistribute income across people's welfare accounts, but these redistributions would be constrained to be of the balanced-budget variety: total (economy-wide) taxes on each of the welfare accounts would be equal to total transfers into each of accounts. The public and private sectors would provide welfare services on an equal footing, setting prices for these services and competing with one another for the custom of the welfare account holders. We argue that moving from the current welfare state systems to a welfare account system may be expected to play a substantial role in reducing unemployment, encouraging labour force participation, promoting skills, reducing governments' budgetary pressures, cushioning people against economic risks, ensuring efficient provision of health and education services, providing social safety nets and redistributing incomes more efficiently.
Keywords: E64; E61; E62; H54; H61; H52; H42; H23; I11; H24; I38; J68; I22; H51; H53; H11; I28; H41; 330; Welfare state; redistribution; social insurance; unemployment; health; education and training; pensions; sickness and disability; Sozialstaat; Reform; Einkommensumverteilung; Theorie